RETRACTED: The effects of listening to healing beat music on adults’ recovery from exposure to stressful stimuli: A randomized controlled trial - Ik-Lyul Bae; Yeon-Suk Kim; Myung-Haeng Hur (Integrative Medicine Research)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal).This article has been retracted at the request of authors.The authors found an error in the measurement and collection of the data in this article, which means the authors do not have confidence in the corresponding results. Concerns were raised over whether the data analyzed in this article were valid and accurate due to the error. The authors apologize for the oversight.To ensure maximum accuracy, the editors and authors concluded to retract this article.